Laparoscopia diagnostica y terapéutica en pacientes con trauma abdominal. - Arias Toctaquiza, Washington Geovanny (2023)
The present abstract aims to demonstrate the usefulness of diagnostic and therapeutic laparoscopy in patients with abdominal trauma through a literature review. The study analyzed the clinical elements and complications associated with the use of laparoscopy in the diagnosis and management of abdominal trauma. The review found that laparoscopy can play a significant role in the diagnosis and treatment of patients with abdominal trauma in specific situations and under certain conditions. Laparoscopic surgery offers advantages such as shorter hospital stays, faster recovery, and a reduction in unnecessary laparotomies in hemodynamically stable patients. The review highlights the usefulness of laparoscopy in identifying and repairing injuries in both penetrating and closed abdominal trauma. These findings support the conclusion that laparoscopy is currently the alternative with the greatest benefit for patients with abdominal trauma compared to conventional surgery. However, it is important to note that there is a possibility of conversion to laparotomy in some cases, which underscores the need for individualized evaluation. Additionally, through the review of national and local studies, it is evident that laparotomy remains the main option in the management of abdominal trauma.